Effect of water on the behaviour of adhesives modified with thermally expandable particles. (August 2018) - Banea, M.D.; da Silva, L.F.M.; Carbas, R.J.C.; Barbosa, A.Q.; de Barros, S.; Viana, G.
Abstract: In this work, the water diffusion in Thermally Expandable Particles (TEPs) modified adhesives was measured and the residual strength of water saturated and desorbed TEPs-modified adhesives was assessed. Bulk specimens were used to measure the diffusion coefficient of water in a TEPs-modified adhesive and tensile dogbone specimens were used to measure the stress-strain curves as a function of water uptake. In addition, the glass transition temperature ( T g ) of aged and unaged TEPs-modified adhesives was measured, and the fracture surfaces of failed tensile specimens were examined using a scanning electron microscopy (SEM). It was observed that the moisture uptake increases as a function of TEPs content. The tensile properties (i.e. strength and elastic modulus) of the TEPs-modified adhesive tend to decrease with increasing water content, which recover after desorption at the same temperature as the initial environmental conditioning.